IMPACT OF INFORMATION ON THE DELIVERY OF CARGO WITH AIR TRANSPORT - Габріелова, Т.Ю.; Войцеховський, В.С. (Science-based technologies, 2013)
Peculiarities of the impact of informatization on the process of cargo delivery involving air transport under conditions of competitive environment dynamic development have been considered. Information products providing uploading capacity on an extensive air route network were analysed. The role of international mediation bodies for financial settlements between participants of air transportation process was determined. Basic aspects of the pricing control depending on the condition of flight load of a network carrier were identified. The experience of implementing innovative SAP-technologies by airline "Aeroflot" as the closest to national realities, as well as the world leader - airline "Lufthansa" was analysed.